Tarawera 1886: an integrated review of volcanological and geochemical characteristics of a complex basaltic eruption. Issue 2 (3rd July 2021) - Rowe, Michael C.; Carey, Rebecca J.; White, James D. L.; Kilgour, Geoff; Hughes, Ery; Ellis, Ben; Rosseel, Jean-Baptiste; Segovia, Amy
ABSTRACT: The cataclysmic basaltic eruption of Mt. Tarawera in 1886 represents a significant cultural and scientific event for New Zealand. This review utilises published and new observations, to reinterpret eruptive parameters encompassing the entirety of the eruption. The ∼17 km eruptive fissure, active for 4+ hours, extends across Mt. Tarawera to the hydrothermally active Waimangu region. Correlating published observations of bed thickness, componentry and microtextures from Mt. Tarawera to new bed descriptions and granulometry for the Rotomahana-Waimangu rift segment allows for a re-assessment of eruption variations along the length of the fissure. Variably thick pyroclastic fall sequences at Mt. Tarawera contrast with the pyroclastic surges and an eruption plume that together deposited the 'Rotomahana Mud' erupted along the Rotomahana-Waimangu segment. Providing insight into pre-eruptive conditions, new mineral chemistry from Mt. Tarawera provides the first constraints on crystallisation pressures (<2 kbar), temperatures (<1100°C), and magmatic water content (<2.8 wt%). Recalculated volumes indicate a bulk eruptive volume of 1.1–1.3 km 3, and a juvenile basalt volume of up to 0.67 km 3, which then lead to calculated discharge rates of 3.7 × 10 7 –7.8 × 10 7 kg s −1 for the northern Mt. Tarawera segment of the fissure and 1.4–5.7 × 10 6 kg s −1 for the Rotomahana segment.